Public and Private Resources in Public Safety (United States): Metropolitan Area Panel Data, 1977 and 1982 - Zedlewski, Edwin W. ([Verlag nicht ermittelbar], 1989)
This data collection provides a series of measures relating to public safety for all SMSAs in the United States at two time periods. Variables include: municipal employment (e.g. number of municipal employees, number of police employees, police payrolls, municipal employees per 10,000 inhabitants), municipal revenue (total debt, property taxes, utility revenues, income taxes), nonmunicipal employment (retail services, mining services, construction services, finance services), crime rates (murder, robbery, auto theft, rape), labor force and unemployment, property value, and other miscellaneous topics.